Aiding and Opposing Re-circulating Mixed Convection Flows in a Square Vented Enclosure. (1st October 2020) - Dhahad, Hayder A.; Al-Sumaily, Gazy F.; Alawee, Wissam H.; Thompson, Mark C.
Abstract: A numerical study is performed to investigate mixed convective flow in a vertically vented square enclosure with heating or cooling one of the vertical walls and the other three walls are insulated. This study is conducted to analyse and clarify the intricate interaction between the buoyancy-induced flow and the pressure-driven external flow in a vertical upward laminar air jet for both assisting and opposing buoyancy situations. The approach of spectral-element that is introduced as a finite-element method with high-order Lagrange polynomials as interpolating functions, is applied to discretise unsteady Navier-Stokes, continuity and energy equations, and for calculating the velocity and temperature fields. The numerical solutions are obtained for air having a Prandtl number of (Pr = 0.7) and for buoyancy parameters which cover the whole mixed convection region, ranging from pure forced convection with a Reynolds number ranging between (10 ⩽ Re ⩽ 350) to pure free convection with a Richardson number ranging between (0 ⩽ Ri ⩽ 30), with a single dimensionless enclosure size. The results reveal that the flow and thermal patterns can be significantly influenced by both aiding and opposing buoyancies. Also, the mean heat transfer rates increase with increasing either the buoyancy force Richardson number or the forced flow Reynolds number in assisting flows. However, in opposing flows, it is found that the mean heat transfer rates decrease with increasing the buoyancy effects for small to moderate (Ri ⩽ 2) but, they begin rising for higher Richardson number when the free convection starts domination the flow.